Usefulness of LED lightings in cereal breeding on example of wheat, barley and oat seedlings - Stefański, Piotr; Siedlarz, Patrycja; Matysik, Przemysław; Rybka, Krystyna (International Journal of Agricultural and Biological Engineering, 2019)
The LED lightings in horticulture is becoming prevalent, due to their physical properties allowing reduction of electricity consumption and on modulation of light spectrum and frequency. At present, LED lightings are not widely used by cereal breeding companies despite the fact that use of greenhouses is very common. This is why, the present experiment was run to show the evidence of LED lightings usefulness in a cereal crops breeding processes. Spring wheat (Triticum aestivum, L.), spring barley (Hordeum vulgare, L.) and oat (Avena sativa, L.), one cultivar of each species, were used for the 9 week trial conducted in a greenhouse with strictly controlled temperature (22oC) and humidity (80%). As a light source, 4 LED illuminators along with a high-pressure sodium and xenon lamps and a natural sunlight in non-shadowed area of the same greenhouse were used. LED illuminators were characterized by relatively high ratio of blue/red radiation (0.6-1.3) to force the stem shortening, since cereal seedlings with such a growth habit are preferred in greenhouse cultivation of cereals. It was evidenced, that LED illuminators provided light suitable for cereals growth in a greenhouse, however each species had slightly different optimal light requirements. For wheat and barley the best impact on stem shortening and also on time to heading had a LED illuminator with high multi wave-blue radiation whereas on the leaves width the illuminator with lowest blue/red ratio. For oat seedlings a light source with highest light intensity and highest blue/red ratio seemed to be the most proper. Not much differences in seedlings growth and time to heading suggested that there is a chance for construction of one universal type of LED illuminator designed for greenhouse stages of cereal crops breeding.Keywords: greenhouse, light emitting diodes, cost-effectiveness, Triticum aestivum, Hordeum vulgare, Avena sativaDOI: 10.25165/j.ijabe.20191206.3646Citation: Stefański P, Siedlarz P, Matysik P, Rybka K. Usefulness of LED lightings in cereal breeding on example of wheat, barley and oat seedlings. Int J Agric & Biol Eng, 2019; 12(6): 32–37.